Abdominal Adiposity and Physical Inactivity Are Positively Associated with Breast Cancer: A Case-Control Study - Godinho-Mota, Jordana C. M.; Goncalves, Larissa; Soares, Leonardo R.; Mota, Joao F.; Martins, Karine A.; Freitas-Junior, Ismael [UNESP]; Freitas-Junior, Ruffo (Hindawi Ltd, 2018)
Objective. To examine whether breast cancer is associated with body composition and level of physical activity, considering the menstrual status. Methods. This was a case-control study with 116 women recently diagnosed with breast cancer and 226 controls. Body composition was assessed by dual-energy X-ray absorptiometry, and cardiometabolic risk was assessed by conicity index and waist-to-height ratio. The short version of the International Physical Activity Questionnaire was used to estimate the level of physical activity. All analyses were adjusted for age and BMI. Results. The total body fat percentage, android body fat, android-gynoid ratio, and waist circumference were positively associated (p < 0.05), whereas the percentage of lean body mass (p < 0.05) and the level of physical activity (p < 0.01) were inversely associated with breast cancer in premenopausal women. Among postmenopausal women, physical activity decreased the chance of developing breast cancer by 49% (95% CI = 0.29 to 0.92, p = 0.02). Conclusion. A low percentage of lean body mass and high abdominal adiposity in the premenopausal period increase the chances of developing breast cancer. Regular physical activity is inversely associated with breast cancer in pre- and postmenopausal women.